PENYAKIT MASA LAMPAU PADA PENDUDUK CARUBAN MASA KLASIK- ISLAM: SUATU TINJAUAN PALEOPATOLOGI - Ashwin Prayudi; Rusyad Adi Suriyanto (Balai Arkeologi Yogyakarta, 2017)
Caruban is a site which emerged between Classical and Islamic period. This site is, located in Lasem District, Rembang Regency, Central Java. In an excavation in 1981, there were three human remains located from this site. This research objective is to find the evidence of diseases from the human remains curated in Laboratory of Bioanthropology and Palaeoanthropology, Gadjah Mada University. This research use paleopathological approach and macrosopic analysis. The results of this research are the individuals age and sex estimation, diseases and its relations with cultural aspects. The cultural influences which reflected in the remains, were dental modification such as dental ablation and dental filing.